2019
DOI: 10.21608/mnj.2019.154362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercises Program on Knee Functional Outcomes for Patients After Arthroscopic Anterior Cruciate Ligament Reconstruction

Abstract: Background: Rupture of the anterior cruciate ligament (ACL) is a common cause of knee instability, requiring ACL reconstructions with about one million completed worldwide annually. Successful (ACL) reconstruction requires physical rehabilitation to help patients return to an active lifestyle. This study aimed toevaluate the effect of exercises program on knee functional outcomes for patients after arthroscopic anterior cruciate ligament reconstruction. Study design: Quasi experimental research design was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…on the other hand, this study is in disagreement with Howe et al, (2021) (24) , they reported that female were at higher risk for ACL rupture than male. Regarding marital status in the present study more than half of the patients in the control and study groups were married These subjects' marital status was similar to AbdElghany et al,(2019) (25) , who reported that that most of their studied sample were married. In relation to educational level, the finding of this study represented that most of both groups were university educated.…”
Section: Discussionsupporting
confidence: 89%
“…on the other hand, this study is in disagreement with Howe et al, (2021) (24) , they reported that female were at higher risk for ACL rupture than male. Regarding marital status in the present study more than half of the patients in the control and study groups were married These subjects' marital status was similar to AbdElghany et al,(2019) (25) , who reported that that most of their studied sample were married. In relation to educational level, the finding of this study represented that most of both groups were university educated.…”
Section: Discussionsupporting
confidence: 89%
“…Rodriguez et al, 2020). The nurse has become a basic element of the rehabilitation process (AbdElghany et al, 2019), contributing to physiological and psychological patient outcomes. Before beginning rehabilitation, the nurse should educate the patient on the significance of adhering to the rehabilitation program and making lifestyle modifications to promote healing.…”
Section: Introductionmentioning
confidence: 99%